2024
DOI: 10.1007/s00417-024-06388-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intraocular pressure-lowering efficacy and safety of ripasudil-brimonidine fixed-dose combination for glaucoma and ocular hypertension: a multicentre, open-label, phase 3 study

Hidenobu Tanihara,
Tetsuya Yamamoto,
Makoto Aihara
et al.

Abstract: Purpose To evaluate the long-term efficacy and safety of ripasudil-brimonidine fixed-dose combination (RBFC), a new intraocular pressure (IOP)-lowering medication for glaucoma and ocular hypertension (OHT). Methods This prospective, multicentre (23 sites in Japan), open-label study enrolled patients with primary open-angle glaucoma (POAG), OHT or exfoliative glaucoma and assigned them to one of four combination therapy cohorts, based on previous treatment(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…It has demonstrated IOP-lowering ability and lower conjunctival hyperemia scores compared to single ripasudil administration [ 55 , 56 ]. A recent prospective phase 3 study of RBFC confirmed its long-term (52 weeks) efficacy and safety, both alone and in combination with other anti-glaucoma agents [ 57 ]. An in vivo study was conducted to treat adult mice with optic nerve injury using topical ripasudil, brimonidine, or a combination of both drugs.…”
Section: Recent Trials Of Rho Kinase Inhibitors In Glaucoma Treatmentmentioning
confidence: 99%
“…It has demonstrated IOP-lowering ability and lower conjunctival hyperemia scores compared to single ripasudil administration [ 55 , 56 ]. A recent prospective phase 3 study of RBFC confirmed its long-term (52 weeks) efficacy and safety, both alone and in combination with other anti-glaucoma agents [ 57 ]. An in vivo study was conducted to treat adult mice with optic nerve injury using topical ripasudil, brimonidine, or a combination of both drugs.…”
Section: Recent Trials Of Rho Kinase Inhibitors In Glaucoma Treatmentmentioning
confidence: 99%